Neural network inferential estimator for product composition of a fatty acid distillation column - Ahmad, Arshad; Wong, Teck Siang (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
This paper discuss the application of a software-based estimator for the measurement of fatty acid composition in a palm oil fractionation process. A typical configuration of a distillation column with a appropriate control loops was simulated using Hysys.Plant dynamic process simulator. The simulation model was proved to be realistic test-bed representing an industrial process since a sufficiently accurate plant/model match was obtained. Using data generated from the simulator, a fatty acid composition estimator was developed using artificial neural networks (ANN). Good estimation of composition was demonstrated.